Pengaruh Keterlibatan Konsumen, Citra Merek, Kemudahan Penggunaan, dan Pemasaran Media Sosial terhadap Tindakan Pasca Pembelian: - Anggraini Norma Sophie Popilin; Nurul Azizah (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine the effect of Consumer Engagement, Brand Image, Ease of Use, and Social Media Marketing on Post-Purchase Actions from Wardah Cosmetics on Instagram @wardahbeauty followers of the Surabaya area, either partially or simultaneously. The population in this study are consumers of Wardah Cosmetics on Instagram @wardahbeauty who are domiciled in Surabaya who have made a purchase transaction at least 2 times. This study used a sample of 100 respondents. In this study using non-probability sampling technique. The data analysis technique uses Multiple Linear Regression analysis method with IBM Statistic 25 software which uses validity test, reliability test and classical assumption test analysis first to make the right regression test. The results of this study indicate that Consumer Involvement, Brand Image, Ease of Use, and Social Media Marketing together have a significant influence on Post-Purchase Actions, where each variable has a positive and significant influence on Post-Purchase Actions, except for the Ease of Use variable which has a negative and insignificant effect on Post-Purchase Actions. Keywords: Consumer Involvement, Brand Image, Ease of Use, Social Media Marketing and Post-Purchase Actions.